What is Socrates’ hypothesis? A proposal for reading Men. 97e2-98b5 - Maffi, Emanuele (Revista Archai, 2023)
Recently, some scholars have authoritatively claimed the idea that Men. 97e2-98b5 is a strong criticism of any epistemological perspective based on an additive model of knowledge, in which knowledge is conceived as a form of opinion with the addition of something else. In this article I try to show that Plato’s aim is not to criticize this model of knowledge but to pose, in the form of a hypothesis which has to be verified in other texts, the main problem of his epistemology: is the logos, or rather the aitias logismos, able to bind opinions so firmly together that they are transformed into that kind of infallible knowledge that is the episteme? In order to justify this interpretation of Men. 97e2-98b5, I try to provide a new reading of the meaning of the relationship between this passage of the dialogue and some topics exposed in the previous sections of the text (such as the maieutic experiment to which Socrates subjects Meno’s slave, the Recollection doctrine and the method by hypothesis).